HUBUNGAN ANTARA HARGA DIRI DENGAN NARSIS PADA REMAJAPENGGUNA PATH - MAULINA, AGITA VERA (2017)
Narcissists is a tendency looking at ourselves to excess and a desire to gain praise and think of yourself most everything. One of the factors that affects narcissists is self-esteem. The purpose of this research is to find.: 1) the relationship between self-esteem with narcissists users path in adolescents. 2) a contribution effective self-esteem with narcissistusers path in adolescents. 3) self-esteem users path in adolescents. 4) narcissists users path in adolescents. Hypothesis advanced by is that there is a positive relationship between self-esteem with narcisstic user path in adolescents. A subject in this study as many as 80 people users path. A population that used in this research is: a) scale self-esteem and b) scale narcissistusers path. Technique analysis the data used in this research was correlation product moment. The result of analysis that I got in accordance with a hypothesis that in purpose that is, there was correlation positive very significant between self-esteem with narcissistusers path in adolescents, on the other hand the lower self-esteem the low narcissistusers path in adolescents. This is apparent from value r = 0,568 with sig 0.000: ((p<0,01)). Contribution effective by selfesteem of 32,26 %. This there are still 67.74% others variable that can affect narcissist users path out variable self esteem. Keywords : narcissist, self-esteem, users path